2016
DOI: 10.1074/jbc.m115.696609
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Chemoresistance and Other Malignancy-related Features of Colorectal Cancer Cells Are Incremented by Ribosome-inactivating Stress

Abstract: Colorectal cancer (CRC) as an environmental disease is largely influenced by accumulated epithelial stress from diverse environmental causes. We are exposed to ribosome-related insults, including ribosome-inactivating stress ( Colorectal cancer (CRC)3 is one of most commonly diagnosed cancers in developed countries, with a high morbidity and mortality rate because of metastasis via hepatic venous drainage from the original tumor mass (1, 2). This enables latestage tumors to endow a very high metastatic potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…To further explore the underlying mechanism, we did the functional enrichment analysis of the candidate genes and genes which are highly correlated with these candidate genes. Our observed enrichment in the cell cycle is in line with previous studies, which suggested the cell cycle pathway is a determinant in the efficiency of CRC therapy [25,26]. The limitation of this study was the lack of the detailed information about the detail distance between tumor tissues and adjacent normal tissues.…”
Section: Discussionsupporting
confidence: 89%
“…To further explore the underlying mechanism, we did the functional enrichment analysis of the candidate genes and genes which are highly correlated with these candidate genes. Our observed enrichment in the cell cycle is in line with previous studies, which suggested the cell cycle pathway is a determinant in the efficiency of CRC therapy [25,26]. The limitation of this study was the lack of the detailed information about the detail distance between tumor tissues and adjacent normal tissues.…”
Section: Discussionsupporting
confidence: 89%
“…For successful chemotherapy in cancer patients, basal level of p53 is very important. 23 Our studies suggest that a high level of FAM213A can reduce oxidative stress through the NRF2/ARE pathway. As a result, reduced oxidative stress inhibits activation of p53, which is important for chemo-sensitivity in chemotherapy.…”
Section: Fam213a Plays a Role In Myelopoiesis In Zebrafish Embryosmentioning
confidence: 62%
“…p53 is a recognized tumor suppressor gene in AML and other solid tumors, and is a representative DNA damage marker . Since uncontrolled oxidative stress can induce DNA damage, we checked the activation of p53 pathway in fam213a MO‐injected embryos.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have indicated that these mutations play distinct roles in development and therapy resistance of CRC [96]. Recently, the effects of the interaction of ribonucleotide reductases with thioredoxin [97] and the influence of the negatively regulated miRNA-mRNA pairs [98] and ribosome-inactivating stress [99] in CRC have been discussed. Taking into account that, as previously mentioned, both ribonucleotide reductases and RNA are targets of TSCs, and previous studies show the attack of CRC cells by TSCs [100,101], it could be interesting to apply these compounds to resistant CRC cells.…”
Section: -Introductionmentioning
confidence: 99%